Analisis Limbah Tumbuhan Fitoremediasi (Typha Latifolia, Enceng Gondok, Kiambang) Dalam Menyerap Logam Berat - Irhamni Irhamni; Setiaty Pandia; Edison Purba; Wirsal Hasan (Fakultas Teknik, 2018)
Research on the ability of plants to reduce and transport pollutants, especially heavy metals to date continues to be done in line with technological developments. Hyperaccumulator plant species are still very limited, therefore research that leads to the search for these types of plants is still very necessary. The author wants to do research on the Result of Measurement of Waste Simulation of Phytoremediation Plant (Typha Latifolia, Enceng Gondok, Kiambang) in absorbing heavy metals.The purpose of this study was to obtain the results of phytoremediation plant measurements on th esimulated waste in absorbing heavy metals. The simulated wastes used for the three plants (Typha Latifolia, Enceng Gondok and Kiambang) are concentrations of 200 ppm, 150 ppm, 100 ppm and initial control. The highest analysis result of the highest measurement was obtained on the waste simulation of typha latifolia with 100 ppm of 25,1 gram and followed by water hyacinth 100 ppmequal to 18,8 gram. Resume from the accumulation of the three plants and the three different waste simulations, the typha latifolia plant has the best measurement results. This proves that typha latfolia plants have high absorption for heavy metals, and is a plant used as one of the heavy metal absorbent plants